Workshop Pendidikan Inklusif Bagi Tenaga Pendidik dan Orang Tua: Pengabdian - Iba Harliyana; Ai Siti Nurmiati; Rasyimah; Siti Aisyah Hanim; Feby Arief Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effectiveness of an inclusive education workshop for educators and parents in improving participants' understanding, attitudes, and skills regarding the application of inclusive education principles. The workshop was implemented through several stages, including planning, implementation, and evaluation. The results of this activity showed a significant increase in participants' level of understanding, with a 30–35% increase in post-test scores compared to the pre-test. Participants no longer interpreted inclusive education as merely accepting students with special needs, but understood the importance of curriculum adaptation, learning differentiation, and fair assessment for all children. The workshop also succeeded in changing participants' attitudes to be more positive and empathetic towards diversity, and strengthened awareness of the importance of collaboration between teachers and parents. In terms of skills, participants demonstrated improved abilities in pedagogical, communication, and socio-emotional aspects through simulation and role-play activities. Overall, this workshop proved effective in building participants' capacity and commitment to creating an inclusive, welcoming, and equitable learning environment for all students.